Development in C++ and python of a time structure Analysis Tool for particle beam analysis for the MINERvA Test beam experiment - Salazar Quiroz, Gerald Fernando (2016)
We present in this thesis the results of the design and programming of a temporal anal- ysis tool for experiment data MINERVA Test Beam (TbTaTool), which receives pions and electrons in the energy range corresponding to the end of the interactions of neutrinos energy states with MINERvA detector. The TbTaTool is independent, flexible and adapt- able to other contexts where we need to analyze the distribution of events over time, because it has separated datasets’ production from the tool itself. Our tool has been applied to the data (Run 2 and Run 3) that the experiment has obtained in MTest at Fer- milab, focusing on the variables of frequency of spill of the particles (MI’s spill frequency), duration of spill (MI’s spill duration) and the profile over time of packets corresponding to the delivery of the particles (time profile). Our calculations show 0.01% of difference for the frequency of spill of the particles and 9.34%, for the second variable, compared to the values indicated by the Fermilab’s Accelerators Division. Furthermore, this tool had set the basis for constructing a real time DAQ visualizator of the measurement process.